PERAN SERIKAT PEKERJA DALAM PROSES PENENTUAN UPAH MINIMUM (UMK) DI KOTA BEKASI TAHUN 2015 - suci meyta wati; yuwanto .; muhammad adnan (Journal of Politic and Government Studies, 2016)
AbstractWages are an important component in employment, that as one element in the implementation ofthe employment relationship, which has a strategic role in the implementation of industrialrelations, basically should be proportional to the contributions already made workers / laborers inproducing goods or services. But wages are felt by laborers / workers is still lacking to meet theneeds of decent living. Therefore, the problem in this research is